Dynamics of job satisfaction around internal migrations: a panel analysis of young people in Britain and Australia - Perales, F (My University, 2017)
There is ample evidence that internal migration is a vehicle for upwards economic and social mobility, particularly amongst young educated people, with studies documenting favourable effects on objective labour market outcomes such as employment status, earnings and occupational standing. However, this literature has been more silent about the potential effects of internal migration on subjective measures of utility. In this paper I use panel data from Australia and Britain and panel regression models to examine whether and how internal migration is associated with young people’s self-reported job satisfaction, paying attention to the time dynamics underpinning the associations. This enables gaining a more holistic picture of the outcomes associated with internal migration during early adulthood. Key findings indicate that long-distance and work-motivated migrations have positive and statistically significant effects on the job satisfaction of young people in Britain and Australia, particularly amongst those who hold university degrees. Additionally, the results reveal time patterns in the ways in which job satisfaction and residential mobility intersect: long-term trends in job dissatisfaction can trigger internal migration, and internal migration can set long-term onwards trends in job satisfaction. I conclude by calling for further research on the outcomes of internal migration on subjective well-being leveraging the properties of panel data and using a life course approach.
Keywords: Employment; Labour market; Employment; Employment and unemployment